{Factors associated with caregiver psychological distress in chronic schizophrenia} - Mitsonis, Charalampos; Voussoura, Eleni; Dimopoulos, Nikolaos; Psarra, Vassiliki; Kararizou, Evangelia; Latzouraki, Eleni; Zervas, Iannis; Katsanou, M.-N. Maria Nefeli (Social Psychiatry and Psychiatric Epidemiology, 2012)
BACKGROUND AND AIMS: Caregivers of patients with schizophrenia experience increased levels of psychological distress. This study investigated the impact of caring for patients with chronic schizophrenia on the mental health status of the caregivers and described the relationship between various socio-demographic and clinical characteristics and caregiving psychological distress.\n\nMETHODS: The study was carried out at the Psychiatric Hospital of Athens. The Symptom Check List Revised (SCL-90-R) was administered to 87 caregivers of chronic schizophrenia patients and 90 healthy controls. The Positive and Negative Syndrome Scale (PANSS) was administered to schizophrenia patients in order to assess illness severity.\n\nRESULTS: The group of caregivers scored higher on the majority of symptom dimensions of the SCL-90-R than the control group. Clinical features of schizophrenia, i.e. duration of illness and PANSS positive and negative symptoms significantly predicted caregiving psychological distress. Caregivers' and patients' socio-demographic characteristics were not associated with caregivers' distress, with the exception of caregivers' sex: female caregivers experienced significantly higher levels of psychological distress than males.\n\nCONCLUSIONS: The study suggests that clinical features of schizophrenia influence distress levels in caregivers of patients with chronic schizophrenia. The stronger predictors of distress appear to be female caregiver's gender, duration of illness as well as positive and negative symptomatology.
Keywords: Caregivers; Chronic schizophrenia; Medicine; Psychological distress; SCL-90-R